Bacteriological profile isolated from cases of otitis media diagnosed at tertiary care hospital of Gujarat, India - Patel, Kirankumar Navnitlal; Shrimali, Gaurishanker P.; Thakor, Nilesh (International Journal of Research in Medical Sciences, 2016)
Background: Otitis media is commonest disease seen in children. Bacteria are responsible for majority of the cases of otitis media. The aim of the study was to speculate the aetiological bacterial flora which was responsible for the cases of otitis media. Methods: The present study was conducted by Department of Microbiology, B. J. Medical College, Ahmedabad, India during 1st May 2000 to 30th April 2002. Before conducting the study approval was obtained from Institutional Ethical Committee for human research. Total 140 patients of otitis media were included after written informed consent. The ear discharge from each diseased middle ear was collected and inoculated on blood agar, MacConkey’s agar and chocolate agar media and were incubated at 37°C for 24 hours. The organisms were identified by using a standard procedure. Data was analyzed using Microsoft exel software (Trial Version). Results: Out of 140 samples 114 (81.43%) had positive culture. out of 114 cases, 64 (56.14%) were male. Majority of the cases (32.45%) were in the age group of 0-14 years. Out of 114 positive cases, single organism was isolated in 99 (86.8%) cases. Out of total 116 strains 44 (37.9%) were gram positive and 72 (62.1%) were gram negative organisms. Among gram positive organisms, Staphylococcus aureus (63.63%) was predominant organisms isolated followed by coagulase negative Staphylococci (20.45%) and among gram negative organism Pseudomonas (69.44%) was predominant organisms isolated followed by proteus species. Conclusions: Staphylococcus aureus and Pseudomonas sp. were found to be the common cause of otitis media in our study.